The Correlation between the Differences in NUCB2/Nesfatin(NES) Peptide Levels and Body Weight, Lenght and Gender in Alburnus tarichi - Caf, Fatma; Koprucu, Sibel; Algul, Sermin; Koyun, Mustafa; Atici, Ataman Altug (Central Fisheries Research Inst, 2018)
Nucleobindin-2 (NUCB2) is a 396-amino-acid peptide related to food intake and body weight. It suppresses appetite by acting on the hypothalamus, andits derived peptide, nesfatin-1, was shown to reduce food intake and body weight in rodents. In this study, we examined NUCB2 peptide levels in correlation with body weight, length and gender in adult Alburnus tarichi fish. Serum NUCB2 levels were measured with ELISA, and were observed to significantly vary depending on gender: 0.43 +/- 0.17 ng/mL in the males (n=6) and 0.28 +/- 0.11 ng/ml in the females (n= 6) (p<0.05). However, NUCB2 levels were not significantly correlated to body weight (r=-0.08, p=0.7) or length (r=-0.16, p= 0.6). NUCB2/nesfatin, an appetiteregulation hormone, was therefore shown to be impacted by gender but not by body weight or length in A. tarichi.
Keywords: NUCB2/nesfatin; Alburnus tarichi; body weight and length; gender; ELISA